Strategi Marketing Politik Hary Tanoesoedibjo Dalam Usaha Membangun Personal Branding Politik - Hartini Basaria Natasya Sitanggang; Awang Dharmawan (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2016)
Today, many people have already used new media for doing their activities, includes communicating. The benefits in opening the edges each humans and using the innovating technology makes the new media usually used by citizen. These concerns are used by the politic consultant to promote some political parties or some candidates. HaryTanoesoedibjo is one of media businessman in Indonesia who tries to take his way becoming a politician. To increase his electability in politic, a politic consultant for HaryTanoesoedibjo should be able to know the right strategies for HaryTanoesoedibjo. This study was made to know what strategies are right for HaryTanoesoedibjo. This research was using the 4Ps and PDB analysis. Besides that, this study was also intended to know the right platform for HaryTanoesoedibjo in case for succeed his way for president election. The datas in this study are from the analysis in social media and website that used by HaryTanoesoedibjo and some available literatures. Keywords: Political Marketing Strategy, New Media, HaryTanoesoedibjo, ABSTRAK Kekuatan media baru sebagai sumber informasi politik, tidak lepas dari perkembangannya sudah menjadi media mainsream yang membangun interaktivitas bagi sesama penggunanya. Hal inilah yang dimanfaatkan oleh konsultan politik untuk mempromosikan partai politik atau kandidat perseorangan. Hary Tanoesoedibjo, sebagai salah satu pebisnis media yang memasuki jalan sebagai politisi. Dalam menaikkan popularitasnya di dunia politik, konsultan politik yang dimiliki oleh Hary Tanoesoedibjo berusaha menerapkan strategi marketing politik, karena mengingat Partai Indonesia Raya (Perindo) dan Hary Tanoesoedibjo sendiri terbilang baru dalam panging politik nasional. Studi ini dibuat untuk mengetahui bagaimana strategi marketing politik dari tim Hary Tanoesoedibjo. Penelitian ini menggunakanan konsep product, place, price, promotion, dan segmentation (4PS) dan positioning, differentiation, dan branding (PDB). Selain itu, studi ini juga ditujukan untuk mengetahui bagaimana platform media baru yang digunakan oleh Hary Tanoesoedibjo sebagai ketua Partai Persatuan Indonesia (Perindo). Kata kunci: Strategi Marketing Politik, Media baru, Hary Tanoesodibjo.